Еще одно замечание к центральной предельной теореме для эргодических цепей - Москальцова, Н.В.; Шуренков, В.М. (Український математичний журнал, 1995)
We obtain sufficient conditions that should be imposed on a functionf in order that, for ergodic Markov chains, the sum 1n‾√∑k=0n−1f(Xk) be asymptotically normal.